Gamification 2015
DOI: 10.4018/978-1-4666-8200-9.ch022
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Fun and Learning in a Serious Game Design

Abstract: This article presents the underlying philosophy of Sustain City, an educational serious game system that engages students, particularly prospective and beginning science and engineering students, in a series of engineering design challenges. Various strategies implemented in Sustain City for achieving a balance of fun and learning are discussed, including narrative-learning synthesis, supplementing the player's actions with feedback, and the development of a sufficient guidance system. The evaluation of Sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This should reduce concerns expressed by others regarding serious videogames and player acceptability. [51][52][53] These findings may be due to the extensive formative work conducted during development to ensure children understood the behavioral procedures and could complete them (e.g., interviews, alpha testing, beta testing). 13 The participation of children in shaping the components likely contributed to the development of a game that appealed to this age group on many levels, including an entertainment level.…”
Section: Discussionmentioning
confidence: 99%
“…This should reduce concerns expressed by others regarding serious videogames and player acceptability. [51][52][53] These findings may be due to the extensive formative work conducted during development to ensure children understood the behavioral procedures and could complete them (e.g., interviews, alpha testing, beta testing). 13 The participation of children in shaping the components likely contributed to the development of a game that appealed to this age group on many levels, including an entertainment level.…”
Section: Discussionmentioning
confidence: 99%
“…These types of games can be used to provide players with goal-focused features while simulating real-world problems. Much research has demonstrated that these educational narrative games can both support student cognitive development 12,13,14,15,16,17 and provide benefits in student assessment 18,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…This integration of work and play has been identified as "flow" by psychologist Mihaly Csikszentmihalyi and is characterized by elevated enjoyment and focused concentration on a task [4]. This strategy of teaching combines the elements of a game to achieve the optimal balance between fun and learning [5]. Additionally, the best way to maximize this flow variable is through a very strong immersion factor.…”
Section: Introductionmentioning
confidence: 99%